English Proficiency and Sequencing Skills in Narrative Writing of Public High School Students - Quijano, Lester John T.; Legaspi, Ma. Judy B. (Philippine Social Science Journal, 2020)
This descriptive-comparative research explored the level of grammar proficiency and sequencing skills in narrative writing of the Grade 7 students. Specifically, it sought to determine the significant difference in the level of grammar proficiency and sequencing skills. The 308 Grade 7 students selected through stratified proportional sampling answered the researcher-made instrument. The findings revealed that the students have a low level of grammar proficiency and average level in sequencing skills as a whole. Moreover, a significant difference exists in the level of grammar proficiency and the level of sequencing skills of students when grouped according to academic performance in English and track, while no significant difference exists when the students are classified according to sex. The results imply that students can sequence events in a narrative. However, they find difficulty in writing grammatically correct sentences. With this, instructional materials may be designed to develop the students’ proficiency in writing.